KARAKTRISTIK PERANGKAT PEMBELAJARAN BLENDED COMMUNITY OF INQUIRY YANG VALID UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS MAHASISWA CALON GURU BIOLOGI - Herdiyana Fitriani; Muhamad Ikhsan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2017)
Abstract: Critical thinking skills are very important to learn because they emphasize how to invite learners to find and build their own knowledge so that learners can develop life skill and be ready to solve problems faced in everyday life. Critical thinking can be trained by applying active learning oriented to learners. Today the development of science and technology (Science and Technology) affect almost all human life in various fields. These developments make it easier for people to access all information. In the world of technology utilization education really helps educators in developing learning so that educators can package and present the material becomes more qualified and varied. Blended Community of Inquiry learning tool developed in this research is a device that mix and match the principles of face-to-face teaching and Internet-based teaching that is packaged in the process of inquiry learning to train critical thinking skills. The purpose of this research is to produce a product of Blended Community of Inquiry learning tool to practice critical thinking skill of biology teacher candidate students that is valid, practical and effective. This research is a development research by adapting 4D development model which includes 4 stages namely: Define, Design, Development and Dessiminate (spreading) stages. The outline of this research is a valid, practical and effective Blended Community of Inquiry instructional product including SAP, LKM, module, test instrument and rubric of critical thinking skill of biology teacher candidate and articles published in accredited national journal. Results